2018
DOI: 10.1016/j.ejc.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Cops and Robbers on intersection graphs

Abstract: The cop number of a graph G is the smallest k such that k cops win the game of cops and robber on G. We investigate the maximum cop number of geometric intersection graphs, which are graphs whose vertices are represented by geometric shapes and edges by their intersections. We establish the following dichotomy for previously studied classes of intersection graphs:• The intersection graphs of arc-connected sets in the plane (called string graphs) have cop number at most 15, and more generally, the intersection … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…While this work provides the first in-depth study of SC and SOC graphs, a number of interesting open questions remain. One such question is motivated by our results on the cop-number of SOC graphs: we showed that SOC graphs are incomparable to most classes identified to have cop number two by Gavenciak et al [19], but we could not show such a result for the class of interval-filament graphs [21]. It seems likely that SOC graphs are contained in this class.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…While this work provides the first in-depth study of SC and SOC graphs, a number of interesting open questions remain. One such question is motivated by our results on the cop-number of SOC graphs: we showed that SOC graphs are incomparable to most classes identified to have cop number two by Gavenciak et al [19], but we could not show such a result for the class of interval-filament graphs [21]. It seems likely that SOC graphs are contained in this class.…”
Section: Resultsmentioning
confidence: 77%
“…The cop number cop(G) of a graph G is the smallest integer k such that the cop-player has a winning strategy using k cop tokens. Gavenciak et al [19] showed that the cop number of outer-string graphs is between three and four, while the cop-number of many other interesting classes of intersection graphs, such as circle graphs and interval filament graphs, is two. We show that the cop number of SOC graphs is two as well.…”
Section: Strict Outerconfluent Graphs Have Cop Number Twomentioning
confidence: 99%
See 1 more Smart Citation
“…For general graphs on n vertices it is known that Ω( √ n) cops may be needed, and the celebrated Meyniel's conjecture [25] states that the cop number of a connected vertex graph is O( √ n). Moreover, exact or approximate values of the cop number of several classes of graphs have been derived so far, including plan graphs [7], bounded genus graphs [55], and intersection graphs [27], just to name a few.…”
Section: Related Literature On "Cops and Robbers" Gamesmentioning
confidence: 99%
“…For example, Aigner and Fromme [12] established that if G is a planar graph, then c(G) = 3. This was a classical study which has been generalized in many topological graphs such as [13,14]. For other examples of CR studies, the readers may look at [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%